Zero prevalence of extended spectrum beta-lactamase-producing bacteria in 300 breeding Collared Flycatchers in Sweden - Järhult, Josef D. (Co-Action Publishing, 2013)
Wild birds are important indicators and potential spreaders of antibiotic resistance. The order Passerines is scarcely studied apart from Corvus sp. but extended spectrum beta-lactamases (ESBLs) has been found in Blackbirds. We tested 300 fecal samples from a well-studied population of Collared Flycatchers (Ficedula albicollis) at the Island of Gotland in Sweden and found no ESBL-producing bacteria. These results support the idea of ‘ecological guild’ as Blackbirds are ground-foraging invertebrate feeders, whereas Collared Flycatchers are aerial insectivores not regularly coming into contact with fecal contaminations and therefore less prone to acquire pathogens spread by the fecal–oral route.